Fate of Escherichia coli O157:H7 and Salmonella in soil and lettuce roots as affected by potential home gardening practices. (19th August 2013) - Erickson, Marilyn C; Liao, Jean; Payton, Alison S; Webb, Cathy C; Ma, Li; Zhang, Guodong; Flitcroft, Ian; Doyle, Michael P; Beuchat, Larry R
Abstract: BACKGROUND: The survival and distribution of enteric pathogens in soil and lettuce systems were investigated in response to several practices (soil amendment supplementation and reduced watering) that could be applied by home gardeners . RESULTS: Leaf lettuce was grown in manure compost/top soil (0:5, 1:5 or 2:5 w/w) mixtures. Escherichia coli O157:H7 or Salmonella was applied at a low or high dose (10 3 or 10 6 colony‐forming units (CFU) mL −1 ) to the soil of seedlings and mid‐age plants. Supplementation of top soil with compost did not affect pathogen survival in the soil or on root surfaces, suggesting that nutrients were not a limiting factor. Salmonella populations on root surfaces were 0.7–0.8 log CFU g −1 lower for mid‐age plants compared with seedlings. E. coli O157:H7 populations on root surfaces were 0.8 log CFU g −1 lower for mid‐age plants receiving 40 mL of water compared with plants receiving 75 mL of water on alternate days. Preharvest internalization of E. coli O157:H7 and Salmonella into lettuce roots was not observed at any time . CONCLUSION: Based on the environmental conditions and high pathogen populations in soil used in this study, internalization of Salmonella or E. coli O157:H7 into lettuce roots did not occur under practices that could be encountered by inexperienced home gardeners. © 2013 Society of Chemical Industry